Dyslipidemia, what's new? - Masson, Walter (Revista del Hospital Italiano de Buenos Aires, 2015)
In recent years, some research and clinical practice guidelines related to the diagnosis and treatment of dyslipidemia, which provided new knowledge (and controversy) about this problem have emerged. In this review, the characteristics of the American “new guidelines” for cholesterol management published by the end of 2013 are described, and they are compared with the traditional recommendations. In addition, recent studies assessing the cardiovascular impact of other lipid-lowering drugs (ezetimibe and nicotinic acid) in patients in secondary prevention treated with statins are analyzed. Finally, new hypolipidemic drugs developed in recent years are mentioned (lomitapide, mipomersen and PCSK9 inhibitors), discussing the mechanism of action, efficacy, side effects and clinical settings where they could be used
Keywords: clinical guidelines; dyslipidemia; niacin; ezetimibe; lomitapide; mipomersen; PCSK9 inhibitors